1992
DOI: 10.1093/clinids/14.1.200
|View full text |Cite
|
Sign up to set email alerts
|

Tsukamurella paurometabolum: A Novel Pathogen Causing Catheter-Related Bacteremia in Patients with Cancer

Abstract: Tsukamurella paurometabolum is a weakly acid-fast, pleomorphic gram-positive bacterium found in soil. Human infection due to this organism has rarely been described, and there are no published accounts of bacteremia. Three cases of bacteremia due to T. paurometabolum and related to long-term use of a central venous catheter in patients with cancer who were receiving chemotherapy are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 9 publications
1
18
1
1
Order By: Relevance
“…Testing for sugar utilization with the API 50 CH system showed excellent correlation with published data based on tests with conventional biochemicals. However, with degradation agars, we found inconsistencies among different studies and with our results (2,24,(34)(35)(36). Moreover, in our study we found discrepancies between different commercial systems.…”
Section: G Aurantiaca Was Renamed Rhodococcus Aurantiacus By Tcontrasting
confidence: 78%
“…Testing for sugar utilization with the API 50 CH system showed excellent correlation with published data based on tests with conventional biochemicals. However, with degradation agars, we found inconsistencies among different studies and with our results (2,24,(34)(35)(36). Moreover, in our study we found discrepancies between different commercial systems.…”
Section: G Aurantiaca Was Renamed Rhodococcus Aurantiacus By Tcontrasting
confidence: 78%
“…Cases of human infection with T. paurometabola are infrequent, nevertheless diagnosis rates are increasing, typically in patients with underlying predisposing factors, including immunosuppression (8,9), chronic pathology (6), and indwelling foreign bodies (10). However, there are a number of reported cases in which infected patients had no underlying factors, with Granel et al (11) describing an inflammatory cutaneous infection in an otherwise healthy individual.…”
mentioning
confidence: 99%
“…The most common Tsukamurella infections in human are indwelling device-related infections, including catheter-related bacteremia, especially that of the central venous catheter (7,10,14,16,17), peritonitis associated with continuous ambulatory peritoneal dialysis (15), and knee prosthesis infection (8). Most cases of human infection reported in the literature were caused by T. paurometabola.…”
mentioning
confidence: 99%